Management of orofacial granulomatosis: A case report (Indian Journal of Case Reports, 2024)
The term orofacial granulomatosis (OFG) was introduced by Wiesenfeld in the year 1985. OFG describes a disease with frequent or persistent edema in the orofacial region. It may be idiopathic or may present as a localized form or generalized form as in Crohn’s disease, tuberculosis, and sarcoidosis. The clinical features include facial or lip swellings, angular cheilitis, oral ulcerations, vertical fissures of lips, gingival enlargement, mucosal tags, and sometimes lymph node enlargement. The diagnosis of OFG is quite challenging and it should be excluded from other granulomatous conditions. The usual treatment for this condition includes corticosteroids, monoclonal antibodies, and tumor necrosis factor-α inhibitors. It has been suggested that intralesional triamcinolone injections are a safe and effective therapeutic strategy in controlling the permanent disfiguring swelling of OFG. Hereby, we present a case of a 34-year-old female patient who reported with swollen upper lips and gingival enlargement.